John Hill (1714?–1775) on 'Plant Sleep': experimental physiology and the limits of comparative analysis. Issue 1 (2nd January 2021) - Begley, Justin
ABSTRACT: The phenomenon of 'plant sleep' – whereby vegetables rhythmically open and close their leaves or petals in daily cycles – has been a continual source of fascination for those with botanical interests, from the Portuguese physician Cristóbal Acosta and the Italian naturalist Prospero Alpini in the sixteenth century to Percy Bysshe Shelley and Charles Darwin in the nineteenth. But it was in 1757 that the topic received its earliest systemic treatment on English shores with the prodigious author, botanist, actor, and Royal Society critic John Hill's The Sleep of Plants, and Cause of Motion in the Sensitive Plant . As the present article aims to illustrate, Hill and his respondents used this remarkable behaviour, exhibited by certain plants, as a lens through which to reassess the nature of vegetables, and to address pressing questions of wider natural philosophical import, particularly the degree of continuity between the structures and functions of plants and animals and whether similar mechanisms necessarily account for related movements in different life forms. These disputes, this paper contends, also had profound methodological implications regarding the proper way to conduct experiments, the extent to which it was acceptable to extrapolate from observations, and the status of causal explanations.